Designing Mobile Applications As Old Money Information Media With Prototyping - Telaumbanua, Maylin Monica; Putra, I Nyoman Tri Anindia; Telaumbanua, Kristian (Jurnal Sifo Mikroskil, 2025)
Old money holds significant historical and cultural value in Indonesia's economic growth. However, access to information about old money remains difficult due to limited documentation and less integrated digital systems. This research aims to design and develop a mobile application that provides information on Indonesian old money and archives while integrating an image recognition-based scanning feature to identify money and display historical details. The method used includes a literature study to collect data on old money history and prototyping the initial application design. The system design applies the UML approach, the interface design is developed using Figma, and the initial development is based on Flutter and Firebase. The research outcome is a prototype application that enables users to access old money information, view archives by year of issue and nominal, and use a scanning feature to recognize images on the back of the money automatically. This application is expected to facilitate public access to historical information about old money in Indonesia while increasing awareness and interest in preserving cultural identity in numismatics.